2007
DOI: 10.1111/j.1469-0691.2007.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunodiagnosis of Echinococcus multilocularis infection

Abstract: Alveolar echinococcosis (AE) is a severe zoonotic disease caused by the metacestode stage of Echinococcus multilocularis. The infection can have fatal consequences in humans if treatment is not provided, so early diagnosis is fundamental for initiating treatment and reducing morbidity and mortality. In addition, detection of the parasite in the definitive host plays a central role in epidemiological studies and surveillance programmes for control of AE. This review presents an overview of the present situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 141 publications
1
40
0
3
Order By: Relevance
“…Moreover, these imaging techniques are unsuitable for diagnosis in isolated communities. Therefore, immunological tests have been considered important methods to confirm clinical findings, to give diagnostic help by providing information on the parasite in case of unclear images, or to survey in areas of endemicity where imaging techniques are not readily available (4,9,11). Previously, we have reported an enzyme-linked immunosorbent assay (ELISA) and an immunoblot analysis (IB) by using recombinant E. multilocularis 18-kDa antigen (Em18), the breakdown product of ezrin-radixin-moesin-like protein (2) that is also known as EM10 (8), EM II/3 (7), or EM4 (10) by the cysteine peptidase, and demonstrated that these two tests have a high potential for differentially diagnosing AE (1,12,16,18).…”
Section: Alveolar Echinococcosis (Ae) Caused By the Larval Stage Ofmentioning
confidence: 99%
“…Moreover, these imaging techniques are unsuitable for diagnosis in isolated communities. Therefore, immunological tests have been considered important methods to confirm clinical findings, to give diagnostic help by providing information on the parasite in case of unclear images, or to survey in areas of endemicity where imaging techniques are not readily available (4,9,11). Previously, we have reported an enzyme-linked immunosorbent assay (ELISA) and an immunoblot analysis (IB) by using recombinant E. multilocularis 18-kDa antigen (Em18), the breakdown product of ezrin-radixin-moesin-like protein (2) that is also known as EM10 (8), EM II/3 (7), or EM4 (10) by the cysteine peptidase, and demonstrated that these two tests have a high potential for differentially diagnosing AE (1,12,16,18).…”
Section: Alveolar Echinococcosis (Ae) Caused By the Larval Stage Ofmentioning
confidence: 99%
“…By fractionation of ES antigens with the help of membrane filtration an ES4 antigen fraction (which was found to be a glycoprotein in nature and was highly reactive) microfilaraemia sera was obtained. W. bancrofti mf ES antigen specific IgE antibody was detected in filariasis and tropical eosinophilia by immunofluorescence assay and ELISA [8]. These studies showed the detection of ES antigen specific IgG+A+M antibodies.…”
Section: Excretory-secretory (Es) Antigensmentioning
confidence: 80%
“…Two new polypeptides of the E. multilocularis metacestode, referred as to Em70 and Em90, have also been identified as potential antigens for the serodiagnosis of AE. For the sero-diagnosis of AE now a day's test mainly based on native and recombinant antigens of the Echinococcus multilocularis protoscolex and/or adults such as rEM4, EM13, Em18,16, Em18, rEm18, rEm18-1, rEm18-2 are used [8]. For effective discrimination between AE and CE patients the first echinococcus component used was Em2.…”
Section: Different Parasite Targeted By Immunodiagnosis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of Cystic Echinococcosis is based currently on the identification of the parasite's structures by imaging techniques, including ultrasound, computerized tomography and magnetic resonance imaging (2). However, imaging techniques are relatively complex, do not always offer a good prospect for early diagnosis, and produce data that are sometimes difficult to interpret, being often confused with those from abscesses and neoplasm.…”
Section: Introductionmentioning
confidence: 99%